2008
DOI: 10.1007/s00424-007-0418-9
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the ergtoxin-1 receptors on the voltage sensing domain of hERG K+ channel by AFM recognition imaging

Abstract: The inhibition of the human ether-à-go-gorelated (hERG) K + channels is the major cause of long QT syndromes inducing fatal cardiac arrhythmias. Ergtoxin 1 (ErgTx1) belongs to scorpion-toxins, which are K + channel-blockers, and binds to hERG channel with 1:1 stoichiometry and high affinity (K d ∼10 nM). Nevertheless, patch-clamp recordings recently demonstrated that ErgTx1 does not establish complete blockade of hERG currents, even at high ErgTx1 concentrations. Such phenomenon is supposed to be consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 57 publications
(83 reference statements)
0
30
0
Order By: Relevance
“…These antibodies have been used extensively in Western blotting, immunohistochemistry, and localization of hERG channels (Cayabyab and Schlichter, 2002;Wang et al, 2004;Chtcheglova et al, 2008); however, they have not been tested for their electrophysiological effects. We evaluated both antibodies at 100 nM against hERG currents in HEK cells.…”
Section: Resultsmentioning
confidence: 99%
“…These antibodies have been used extensively in Western blotting, immunohistochemistry, and localization of hERG channels (Cayabyab and Schlichter, 2002;Wang et al, 2004;Chtcheglova et al, 2008); however, they have not been tested for their electrophysiological effects. We evaluated both antibodies at 100 nM against hERG currents in HEK cells.…”
Section: Resultsmentioning
confidence: 99%
“…Applying this technique, VE-cadherin-binding sites on fixed endothelial cells could be identified at a lateral resolution close to 5 nm [4]. In the present study, using living human vascular endothelial cells (EA.hy926 cell line) known to respond to aldosterone [23] and to be capable of expressing the classical intracellular mineralocorticoid receptor (this study), we tried to find out whether specific binding sites for aldosterone were identifiable on the apical cell membranes.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have visualized the localization of membrane proteins such as sodium pump (Jiang et al, 2009) and glucose-transporters (Chtcheglova et al, 2008) on native cell membranes at the single-molecule level using antibody binding. Recognition imaging of cadherin in living cells using an AFM cantilever with a coupled anti-cadherin antibody has shown that individual cadherin molecules form oligomers in the presence of Ca…”
Section: Discussionmentioning
confidence: 99%